2019
DOI: 10.7150/thno.30701
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Downregulation of miR-4306 serves as a New Therapeutic Target for Triple Negative Breast Cancer

Abstract: Rationale: Triple-negative breast cancer (TNBC) is characterized by the absence of estrogen receptor alpha (ER-α), human epidermal growth factor receptor 2 (HER2) and progesterone receptor (PR) expression, but the effect of lacking the three factors on TNBC is unclear. Whether loss of the three factors contributes to deregulate genes that participate in the progress of TNBC remains unknown. Methods: We performed microRNA arrays and comprehensive analysis to screen for miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…MiRNAs have been frequently reported to play key roles in the development and progression of various cancers 37, 38. Our previous studies revealed that miR-509-3-5p expression is markedly low in gastric cancer tissues and is negatively correlated with tumor differentiation, disease stage and T stage, implying that miR-509-3-5p acts as a tumor suppresser in gastric cancer 39.…”
Section: Discussionmentioning
confidence: 95%
“…MiRNAs have been frequently reported to play key roles in the development and progression of various cancers 37, 38. Our previous studies revealed that miR-509-3-5p expression is markedly low in gastric cancer tissues and is negatively correlated with tumor differentiation, disease stage and T stage, implying that miR-509-3-5p acts as a tumor suppresser in gastric cancer 39.…”
Section: Discussionmentioning
confidence: 95%
“…SIX1 has been implicated in various cancers including HCC 28 , 29 . It has been reported that SIX1 is overexpressed in HCC tissues and positively associated with venous infiltration, TNM stage and poor overall survival rate 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging studies have confirmed that different miRNAs play diverse roles in TNBC, some as tumorigenic agents, and some as tumor inhibitors. For example, as tumorigenic agents, miR-25, 16 miR-20, 17 miR-224, 18 miR-135 19 and miR-301 20 promote the occurrence and development of TNBC, whereas miR-124, 15 miR-4417, 21 miR-4306, 22 miR-199, 23 miR-1287 24 and miR-3178 25 as tumor inhibitors inhibit the oncogenesis and development of TNBC. In this study, relative miR-153 expression in TNBC tissues and cells was remarkably lower than that in corresponding adjacent noncancerous tissues and normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%